Causal effect of immune cells, metabolites, cathepsins, and vitamin therapy in diabetic retinopathy: a Mendelian randomization and cross-sectional study - Zhou, Huijun; Wang, Jingzhi; Cui, Xuehao (Frontiers in Immunology, 2024)
Diabetic retinopathy (DR) is a major microvascular complication of diabetes and a leading cause of blindness worldwide. The pathogenesis of DR involves complex interactions between metabolic disturbances, immune cells, and proteolytic enzymes such as cathepsins (CATs). Despite various studies, the precise roles of different CATs, metabolites, and vitamins in DR remain unclear.In this study, we employed Mendelian Randomization (MR) to assess causal relationships using genetic instruments selected based on genome-wide association studies (GWAS). We employed two-sample and mediation MR to explore the causal effects between nine CATs, immune cells, metabolites, vitamins, and DR. Additionally, the study also incorporated data from the NHANES survey to explore the associated relationship between vitamins and DR. We utilized cross-sectional data from the NHANES to analyze the association between vitamin intake and diabetic retinopathy (DR), adjusting for potential confounders to strengthen the validity of our findings.The MR analysis identified CAT H as a significant risk factor for both NPDR and PDR, with no evidence of reverse causality. Additionally, 62 immune cell traits were found to have causal relationships with NPDR and 49 with PDR. Enrichment analysis revealed that metabolic pathways such as sphingolipid metabolism are crucial in DR progression. Vitamins B6 and E were significantly associated with a reduced risk of PDR. Cross-sectional data indicated that vitamins B1, B2, B6, B12, and E progressively decreased with DR severity.This study is the first to identify CAT H as a key risk factor for DR, while vitamins B6 and E showed significant protective effects, particularly against PDR. These findings suggest that CAT H, along with vitamins B6 and E, could serve as therapeutic targets for DR. Further validation through larger, multi-center studies is recommended to enhance the accuracy and applicability of these findings.